Strengthening Customer Loyalty through Customer Engagement, Customer Experience, and Service Innovation - Wijono, Frederick Dewantara; Efrata, Tommy Christian (Jurnal Entrepreneur dan Entrepreneurship, 2023)
The purpose of this study is to ascertain how customer engagement, customer experience, and service innovation impact customer loyalty. This study employs quantitative research techniques, and SmartPLS 3.0 is used for data processing. Non-probability sampling is used with purposeful sampling media, and questionnaires with a linear scale are used to collect the data. The study’s target audience consists of Indonesian citizens who are at least 18 years old, have smartphones with the Gojek app installed, and have used Gojek services at least once. 243 participants made up the study’s sample size. According to the study’s findings, efficiency and user-friendliness of the customer experience have a significant impact on how engaged customers are with Gojek, while service innovation and the sensory component of the customer experience do not. Customer engagement and user-friendliness of the customer experience do not significantly affect customer loyalty for Gojek, but service innovation and the sensory and efficiency of the customer experience do. According to the study’s findings, businesses should concentrate more on enhancing service innovation, sensory quality, and efficiency in order to increase customer loyalty.